Submarine Mass Movements and Their Consequences - Mosher, David C.; Shipp, R. Craig; Moscardelli, Lorena; Chaytor, Jason D.; Baxter, Christopher D. P.; Lee, Homa J.; Urgeles, Roger; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Recent global events such as the devastating 1998 Papua New Guinea tsunami, the 2004 Sumatran tsunami and the 2006 SE Asia undersea network cable failure underscore the societal and economic effects of submarine mass movements. These events call upon the scientific community to understand submarine mass movement processes and consequences to assist in hazard assessment, mitigation and planning. Additionally, submarine mass movements are beginning to be recognized as prevalent in continental margin geologic sections. As such, they represent a significant if not dominant role in margin sedimentary processes. They also represent a potential hazard to hydrocarbon exploration and development, but also represent exploration indicators and targets. This volume consists of a collection of the latest scientific research by international experts in geological, geophysical, engineering and environment aspects of submarine mass failures, focussed on understanding the full spectrum of challenges presented by submarine mass movements and their consequences.
Foreword -- Summary -- 1. Application of new technologies and techniques in the study of mass transport deposits -- 2. Role of mass transport deposit occurrence in margin configuration -- 3. Mass waste evolution: From slumps and slides to distal turbidites -- 4. New approaches on slope stability analysis -- 5. Monitoring pore pressures in submarine slopes and sediment physical properties -- 6. Mass transport deposits in volcanic island settings -- 7. Mass transport deposits and their tsunamigenic risk -- 8. Impact of mass transport deposits in benthic ecosystems -- 9. Impact of mass transport deposits on sea floor structures / risk and mitigation -- 10. Mass transport deposits and its role in offshore hydrocarbon field development -- 11. Current challenges in the study of mass transport deposits and future directions -- 12. Triggering mechanisms of submarine mass movements -- Author Index.
Keywords: Geography; Oceanography; Physical geography; Earth Sciences; Oceanography; Physical Geography